The Effectiveness Of Spiritual Emotional Freedom Technique In Reducing The Incidence Of Postpartum Blues In Pregnant Women - Mubarok, Rahma Zakia; Mustikawati, Irma Finuria; Septianawati, Paramita; Immanuel, Glorio (Syntax Corporation Indonesia, 2024)
Despite the joy of being pregnant, some mothers experience anxiety and depression after giving birth. Blues Depression and anxiety throughout pregnancy and after have a significant negative influence on pregnant women's mental health. This research reviewed the available literature. Electronic databases, including Pubmed, Google Scholar, and ProQuest, were used for the searches. Journals containing the terms